Derivatives with the -ānka suffix as a mirror of cultural development - Milanović Aleksandar M. (Južnoslovenski Filolog, 2020)
The paper analyses the etymology, time of origin, derivational categories and derivational types of derivatives with the -ānka suffix, their number, functions and status in the former and contemporary Serbian language. It is ascertained that they predominantly originated in the late 18th and 19th centuries, that they are a reflection of the social and cultural progress of the Serbs in various areas of material and nonmaterial culture, and that the derivational types involving this suffix were especially productive in the (pre-)Romantic poetic language. The paper also points to the partial productivity of this suffix in contemporary Serbian, its inclination towards terminologisation, as well as to the fact that some derivatives have been relegated to the sphere of archaisms and historicisms.